A functional centromere lacking CentO sequences in a newly formed ring chromosome in rice. (20th December 2016) - Yang, Rui; Li, Yafei; Su, Yan; Shen, Yi; Tang, Ding; Luo, Qiong; Cheng, Zhukuan
Abstract: An awned rice ( Oryza sativa ) plant carrying a tiny extra chromosome was discovered among the progeny of a telotrisomic line 2n+4L. Fluorescence in situ hybridization (FISH) using chromosome specific BAC clones revealed that this extra chromosome was a ring chromosome derived from part of the long arm of chromosome 4. So the aneuploidy plant was accordingly named as 2n+4L ring. We did not detect any CentO FISH signals on the ring chromosome, and found only the centromeric probe Centromeric Retrotransposon of Rice (CRR) was co-localized with the centromere-specific histone CENH3 as revealed by sequential FISH after immunodetection. The extra ring chromosome exhibited a unique segregation pattern during meiosis, including no pairing between the ring chromosome and normal chromosome 4 during prophase I and pre-separation of sister chromatids at anaphase I.